Оцінка стоматологічного статусу дітей-інвалідів із патологією органів дихання - Гавриленко, Марина Аркадіївна; Gavrilenko, M. A. (My University, 2014)
Було обстежено 70 дітей-інвалідів віком 2-18 років із хворобами органів дихання, які періодично лікуються в КУ «Обласна дитяча клінічна лікарня» м. Запоріжжя. Виявлено низький рівень гігієни порожнини рота, високу поширеність захворювань твердих тканин зубів та зубощелепних аномалій. In modern literature dependence of dental status on somatic health is proved. This especially applies to disabled children with respiratory diseases. The situation is further complicated by the fact that this category of children often takes antibacterial and hormonal drugs, has a problem with nasal breathing, and undergoes treatment of the underlying disease in the hospital for a long time, with short periods of remission. Materials on the prevalence and intensity of oral cavity diseases in this group of children are sporadic and inconsistent. Aim of the research: 1. to study the state of oral hygiene in disabled children with respiratory pathology; 2.to examine the state of hard dental tissues in disabled children with respiratory pathology; 3.to study the presence of dentoalveolar anomalies in this category of children.
Evaluation of dental status in disabled children with respiratory pathology
Keywords: діти-інваліди з патологією органів дихання; зубощелепні аномалії; ускладнений карієс; низький рівень гігієни порожнини рота; disabled children with respiratory pathology; dentofacial anomalies; complicated caries; low level of oral hygiene